The Recreational and Developmental Environment`s Role in Restoring Adolescent Potential - Tetyana Svatenkova; Oleksandr Svatenkov (Global Journal of Human-Social Science, 2024)
Recreation leisure and sports play an important role in adolescent communities Their benefits include improving individual health and well-being facilitating developmental opportunities and interpersonal relationships People of all ages abilities and skill levels individually or small groups teams whole communities can be involved in recreation leisure and sporting activities The recreation leisure and sporting activities vary considerably depending on the local context and reflect social systems and cultural values Rest is vital for any age Especially essential during the personality formation period in adolescence Socialization opportunities through recreation are necessary to support social-emotional maturity in healthy adulthood Useful entertainment skills like any life skill requires a well-planned training and support program The article reveals the development environment s organization peculiarities for the individual s psychological potential activation within the adolescent recreation process framework